2020
DOI: 10.1371/journal.pone.0232576
|View full text |Cite
|
Sign up to set email alerts
|

Routine viral load monitoring and enhanced adherence counselling at a public ART centre in Mumbai, India

Abstract: Background Routine viral-load (VL) measurements along with enhanced adherence counselling (EAC) are recommended to achieve virological suppression among people living with HIV/AIDS (PLHA) on anti-retroviral therapy (ART). The Mumbai Districts AIDS Control Society along with Mé decins Sans Frontières has provided routine VL measurements and EAC to PLHA on ART at King Edward Memorial (KEM) hospital, Mumbai since October-2016. This study aims to describe the initial VL results and impact of EAC on viral suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…12 A recent study showed a virological failure of 12% in Mumbai at the beginning of the viral load monitoring, while a suppression of 92% was observed among the subgroup of PLHIV tested for routine monitoring. 7 Developing countries have reported prevalence ranging from 9% to 13% for virological failure among PLHIV accessing antiretroviral therapy. [13][14][15] This may be attributed to the differences in study design, age groups, duration on ART, drug regimen, treatment adherence, study period and definition of virological failure considered for analysis in all these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 A recent study showed a virological failure of 12% in Mumbai at the beginning of the viral load monitoring, while a suppression of 92% was observed among the subgroup of PLHIV tested for routine monitoring. 7 Developing countries have reported prevalence ranging from 9% to 13% for virological failure among PLHIV accessing antiretroviral therapy. [13][14][15] This may be attributed to the differences in study design, age groups, duration on ART, drug regimen, treatment adherence, study period and definition of virological failure considered for analysis in all these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Higher risk of virological failure was observed among men as compared to women similar to a study from western India and other developing countries though few studies have not reported any association. 7,13,15 The reasons for vulnerability of men to virological failure might be due to less healthcare-seeking behaviours and ART uptake, higher body mass index as compared to women which is more likely to maintain a lower concentration of drugs in their bodies than women, and socio culture habits like smoking and drinking which can lead to poorer adherence to medication and virological suppression. [16][17][18][19][20] PLHIV less than 40 year had significant risk of virological failure as found in southern Indian study and Ethiopian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced adherence intervention was introduced along with HIV viral load monitoring has played a signi cant role to improve virologic outcomes in patients who have high viral loads >1000copies/ml and adherence issues [18,19]. WHO guidelines recommend that patients with HVL>1000copies/ml be subjected to an enhanced adherence support intervention, after which a second viral load test should be performed prior to the decision on con rmed virologic failure and the subsequent ARV regimen [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…a 12-month VL is a VL collected between 10 and 14 months). The age variable was categorised into the following ages in years; children (0-9), adolescents (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), young adults (20)(21)(22)(23)(24), adults and elderly (above 50). The outcome of our study was VL suppression.…”
Section: Data Sources and Study Variablesmentioning
confidence: 99%